2011
DOI: 10.1016/j.janxdis.2011.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Anorexia nervosa and generalized anxiety disorder: Further explorations of the relation between anxiety and body mass index

Abstract: We explore comorbidity of anorexia nervosa (AN) and generalized anxiety disorder (GAD) and their relation with body mass index (BMI) and evaluate the presence of fasting and excessive exercise which both have anxiolytic and weight loss effects. All participants were female: 32 with AN only, 607 with GAD only, 22 with AN and GAD (AN+GAD), and 5,424 with no history of AN or GAD (referent) from the Swedish Twin study of Adults: Genes and Environment (STAGE). Lowest adult BMI differed significantly (p < .001) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 22 publications
1
48
0
Order By: Relevance
“…Studies have revealed a strong genetic contribution to eating disorders. Given the high comorbidity of AN and BN with anxiety and depressionlike symptoms (Ivarsson et al, 2000;Thornton et al, 2011), BDNF is a gene of interest in feeding behavior and weight (Rask-Andersen et al, 2010).…”
Section: Brain-derived Neurotrophic Factor and Eating Disordersmentioning
confidence: 99%
“…Studies have revealed a strong genetic contribution to eating disorders. Given the high comorbidity of AN and BN with anxiety and depressionlike symptoms (Ivarsson et al, 2000;Thornton et al, 2011), BDNF is a gene of interest in feeding behavior and weight (Rask-Andersen et al, 2010).…”
Section: Brain-derived Neurotrophic Factor and Eating Disordersmentioning
confidence: 99%
“…As the illness is often protracted, low BMI and the avoidance of eating to restore healthy weight are primary factors influencing high morbidity and mortality that distinguish this illness. Low weight (and the permissive factors involved) are of interest for additional reasons as these are key aspects of AN; moreover, low body weight is the primary distinguishing diagnostic feature separating AN from bulimia nervosa (BN; American Psychiatric Association, 2013) and is associated with other clinical phenotypes, anxiety in particular (Dellava et al, 2010; Thornton et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…[ 15] Specifically, comorbidity estimates for GAD and AN have suggested up to 40% of women with AN also have a lifetime history of GAD. [1] Women with AN were more than six times more likely than women without AN to have GAD [4,6] and, conversely, women with GAD were approximately six times more likely to have AN than women without GAD. [6] Anxiety disorders tend to predate the development of AN, [2,5,7] making it likely that GAD would precede AN and biologically plausible that GAD and AN share some genetic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Along with high comorbidity, the notion that GAD and AN share some common factors is supported by similar characteristics shared by women with GAD and AN. For example, it has been hypothesized that caloric restriction [6,8,9] and exercise [10,11] are anxiolytic for some individuals. Within women with AN, a relationship between high childhood anxiety and low body mass index (BMI) in the context of AN was mediated through caloric restriction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation